Three New Reports of Subsocial Tortoise Beetles From South America (Chrysomelidae: Cassidinae). (3rd September 2015) - Macedo, Margarete V.; Flinte, Vivian; Abejanella, André; Chaboo, Caroline S.
Abstract : Subsociality is known in 35 species in 10 genera of the chrysomelid subfamilies Cassidinae and Chrysomelinae. In Cassidinae, the behavior is clustered in two tribes, Eugenysini and Mesomphaliini, but unknown biologies of many of these species limit fine-scaled resolution of the origins and diversity of this interesting behavior. We report three new records of subsocial Cassidinae, Eugenysa martae Borowiec in Colombia, Omaspides (Omaspides) clathrata L. in French Guiana, and Paraselenis (S.) aulica in Brazil. Females guard larvae and pupae; larvae retain exuvio-fecal shields in some stages. Longer-term study of P. (S.) aulica on the host Ipomoea (Convolvulaceae) revealed that eggs, larvae, and pupae are gregarious and guarded by the female. Larvae lose the defensive exuvio-fecal shields in older instars. Females will mate despite being occupied with brood care. A wasp, Emersonella sp. (Hymenoptera: Eulophidae), and a tachinid fly (Diptera) were observed associated with and reared from juveniles. Our report increases the dataset of documented subsocial cassidines to 26 species, with 23 in Mesomphaliini and three in Eugenysini.